Improving the Quality of Maronggi Products as an Organic Food Commodity on the Home Industry in Jember - Lia Rachmawati; Muhammad Rijalus Sholihin (TGO Journal of Community Development, 2023)
This research was carried out to improve the quality of maronggi products as an organic food commodity in home industries in Jember Regency. The business partner in the Community Partnership (PKM) program is the Maronggi Processing House which processes Moringa leaves (Mrs. Halima/Owner. From an operational perspective, this partner is still relatively simple. For business partners who process Moringa leaves, the equipment used is still manual, the manufacturing process which is still simple, it is not efficient in terms of time and energy and there is no product label and the financial management system is also not in accordance with regulations. From a marketing perspective, Maronggi Processed House uses direct selling and there is a lack of innovation such as using a marketplace (shopee, tokopedia or website ). Apart from that, in terms of packaging, it is not very attractive to consumers, so a label with a design that suits the product must be added. Then there is still no business entity that is standardized by BPOM. Maronggi house producers do not carry out the recording process according to standards due to lack of educational background and human resources. competent. This can be seen from the financial records implemented, namely that business financial management is integrated with household financial management. So, in terms of financial management, partners have difficulty knowing their financial position.